2016
DOI: 10.1002/pmic.201600118
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phosphoproteomic analysis of the PI3K-regulated signaling network

Abstract: The PI3K pathway is commonly activated in cancer. Only a few studies have attempted to explore the spectrum of phosphorylation signaling downstream of the PI3K cascade. Such insight, however, is imperative to understand the mechanisms responsible for oncogenic phenotypes. By applying MS-based phosphoproteomics, we mapped 2509 phosphorylation sites on 1096 proteins, and quantified their responses to activation or inhibition of PIK3CA using isogenic knock-in derivatives and a series of targeted inhibitors. We un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This was an expected observation since previous studies have reported a similar phosphotyrosine enrichment profile using metal ion enrichment chromatography despite significant induction of cellular tyrosine phosphorylation, for instance, via pervanadate treatment [ 34 , 35 ]. Additionally, singly phosphorylated peptides were more strongly represented than doubly or triply phosphorylated peptides in our dataset, consistent with previous reports [ 33 , 36 , 37 ] (Fig. 2d ).…”
Section: Resultssupporting
confidence: 93%
“…This was an expected observation since previous studies have reported a similar phosphotyrosine enrichment profile using metal ion enrichment chromatography despite significant induction of cellular tyrosine phosphorylation, for instance, via pervanadate treatment [ 34 , 35 ]. Additionally, singly phosphorylated peptides were more strongly represented than doubly or triply phosphorylated peptides in our dataset, consistent with previous reports [ 33 , 36 , 37 ] (Fig. 2d ).…”
Section: Resultssupporting
confidence: 93%
“…Future work will be important to more fully dissect the interaction between NT5C and the Arp2/3 complex and its role in PI3K-regulated cell motility. Our study adds to the growing realization that PI3K pathway activation in cells leads to an extensive remodelling of the transcriptome and proteome46525354, a phenotype referred to as a ‘butterfly effect’5355.…”
Section: Discussionmentioning
confidence: 78%
“…One of the first phosphoproteomics studies intensively monitored phosphorylation dynamics in HeLa cells upon treatment with Epidermal Growth Factor (EGF) already in 2006 [9]. Phosphoproteomics has also been used to study various oncogenic signaling pathways such as Ras signaling [10] and PI3K signaling [11]. It has been applied to study lung cancer [12,13], ovarian cancer [14], neuroblastoma [15,16], and many other cancer entities.…”
Section: Introductionmentioning
confidence: 99%